Peran Program Kuliah Kerja Nyata dalam Meningkatkan Edukasi Keuangan Syariah pada Pelaku Usaha Mikro (Studi Kasus Desa Jaharun B Kec. Galang Deli Serdang Sumatera Utara) - Muhammad Ihsan Al Hayyu; Ali Safran Pasaribu; Farras Fadhilah; Miswar Rasyid Rangkuti (Jurnal Ekshis, 2026)
The Community Service Program (Kuliah Kerja Nyata / KKN) represents a practical implementation of the Tri Dharma of Higher Education, particularly in fostering community engagement and empowerment. This study aims to analyze the role of the KKN program in improving Islamic financial literacy among micro-enterprise actors. The research employs a qualitative descriptive approach, allowing for an in-depth understanding of participants’ experiences and program impact. Data were collected through interviews, observations, and documentation, involving six informants consisting of micro-enterprise actors and student participants. The findings indicate that the KKN program plays a significant role in enhancing participants’ understanding of fundamental Islamic financial concepts. These include basic financial management, simple bookkeeping practices, and the application of ethical business values such as honesty (shiddiq), trustworthiness (amanah), fairness (‘adl), and transparency. The educational approach adopted by students is participatory and contextual, enabling micro-enterprise actors to easily comprehend and directly apply the knowledge in their daily business activities. Furthermore, the program contributes to increasing awareness of the importance of separating personal and business finances, planning cash flow, and avoiding practices that contradict Islamic principles, such as riba (interest).